Activity Of Master Craftsmans In Surkhandarya - Mamarajabov Gairat Abdulkhakimovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides information about the development of many craft centers in the oasis and the employment of residents due to the reforms implemented in the Surkhan oasis for the development of the national craft sector.